Learning English Through Duolingo: Narrating Students’ Experience During Covid-19 Pandemic Time - Nadhifah, Umi Nada; Puspitasari, Dewi (Universitas Cokroaminoto Palopo, 2021)
This study aims to narrate students experience during learning English in COVID-19 pandemic particularly by using Duolingo as a self-learning. Semi-structured interview is used to collect the data. By using the thematic analysis of Braun and Clark, two themes of findings indicate that during the use of Duolingo, the beginner students feel satisfied because it is easy to use and to help them in English basic structure, and for intermediate students, Duolingo did not really support them to improve their skill.